A potential with low point charges for pure siliceous zeolites. Issue 20 (15th June 2015) - Sahoo, Sudhir K.; Nair, Nisanth N.
<x xml:space="preserve">Abstract</x> A modified CHARMM force‐field (ZHB potential) with low point charges for silica was previously proposed by Zimmerman et al. (J. Chem. Theory Comput. 2011, 7, 1695). The ZHB potential is advantageous for quantum mechanics/molecular mechanics simulations as it minimizes the electron spill‐out problems. In the same spirit, here we propose a modified ZHB potential (MZHB) by reformulating its bonding potential, while retaining the nonbonding potential as in the ZHB force‐field. We show that several structural and dynamic properties of silica, like the IR spectrum, distribution functions, mechanical properties, and negative thermal expansion computed using the MZHB potential agree well with experimental data. Further, transferability of MZHB is also tested for reproducing the crystallographic structures of several polymorphs of silica. © 2015 Wiley Periodicals, Inc.